ALGEBRAIC THEORY OF DIFFERENTIAL EQuATIONS - MALCOLM A H MACCALLUM; ALEXANDER V MIKHAILOV (U K CAMBRIDGE UNIVERSITY PRESS, 2009)
A unique introduction to the subject, reflecting different approaches to the integration of differential equations.
Keywords: Algebric Number Theory -- Differential Equations -- Differential Calculus -- Differential Algebra